THE RECONSTRUCTION OF ISLAMIC FAMILY LAW FROM THE PERSPECTIVE OF MAQASHID AL-SHARIA - Syukrawati Syukrawati; Eva Ardinal; Nadiah Ismail (Yayasan Adra Karima Hubbi, 2026)
This study stems from the ongoing social changes and transformations in Islamic family law, which necessitate normative reform to align with the principles of maqashid al-sharia. The objective of this study is to examine the role of the concept of maqashid al-sharia as a foundation for the reconstruction of Islamic family law, while also formulating a direction for legal development that is more adaptive to the needs of modern society. This study employs a qualitative method with a juridical-normative approach through a literature review encompassing fiqh literature, statutory regulations, and the thoughts of contemporary scholars, which are subsequently analyzed descriptively and analytically. The research findings indicate that the reconstruction of Islamic family law based on maqashid syariah is capable of strengthening the aspect of public interest by prioritizing the protection of religion, life, intellect, lineage, and property, thereby making family law more flexible and responsive to social dynamics without abandoning the fundamental principles of Sharia. In the discussion, the maqashid syariah approach is viewed as providing a broader scope for ijtihad in the process of renewing Islamic family law, particularly regarding marriage, divorce, and women’s rights, while maintaining a balance between normative texts and evolving social realities. The conclusion of this study confirms that the reconstruction of Islamic family law based on the maqashid al-sharia is an urgent necessity for the realization of a legal system that is more just, humane, and relevant to the demands of the times.